Pain Management in Pregnancy: Multimodal Approaches - Shah, Shalini (Pain Res Treat, 2015)
Nonobstetrical causes of pain during pregnancy are very common and can be incapacitating if not treated appropriately. Recent reports in the literature show that a significant percentage of pregnant women are treated with opioids during pregnancy. To address common pain conditions that present during pregnancy and the available pharmacological and nonpharmacological treatment options, for each of the pain conditions identified, a search using MEDLINE, PubMed, Embase, and Cochrane databases was performed. The quality of the evidence was evaluated in the context of study design. This paper is a narrative summary of the results obtained from individual reviews. There were significant disparities in the studies in terms of design, research and methodology, and outcomes analyzed. There is reasonable evidence available for pharmacological approaches; however, these are also associated with adverse events. Evidence for nonpharmacological approaches is limited and hence their efficacy is unclear, although they do appear to be primarily safe. A multimodal approach using a combination of nonpharmacological and pharmacological options to treat these pain conditions is likely to have the most benefit while limiting risk. Research trials with sound methodology and analysis of outcome data are needed.